Long-term morphological evolution of urban pocket beaches in Montevideo (Uruguay): impacts of coastal interventions and links to climate forcing - Gutiérrez,Ofelia (2015)
Two pocket beaches, Ramírez and Pocitos (Montevideo, Uruguay) are analyzed to assessing their evolution (erosion/accretion) associated with human interventions and climatic forcings from 1927-2008. A multitemporal study was conducted using GIS, long series of aerial photos, satellite imagery, survey of historical background, and statistical analysis. Qualitative indicators of the stability of the beach area are proposed. The relevance of this methodology is analyzed on beaches whose fluctuations tend to mask their long-term evolution. Both beaches remain relatively stable but fluctuating since 1927, with slight loss of surface, especially in Ramírez. The influence of the following factors is discussed: i) human interventions; ii) ENSO events; iii) storm surges; iv) changes in beach area according to the Bruun rule and rising sea level in Montevideo. Although the four of them appear to have acted in different periods, the evidence is not conclusive regarding their relative quantitative importance. This article highlights the importance of using long series of remote sensing and historical analysis to interpret processes linked to inertia of the past in environments that have been modified from longstanding. The trend analysis of these two urban pocket beaches allows to infer that their resilience has not been affected yet, which would allow them to face not extreme climatic stressors. For the purpose of better management it is recommended to: i) conduct continuous monitoring; ii) minimize the actions of mechanized cleaning and sand losses by leakage or removal; iii) implement the reconstruction of natural structures such as primary dunes; and iv) apply the methodology explained in this paper in other Montevideo urban beaches to better understand the climate forcings.